2014
DOI: 10.12681/mms.678
|View full text |Cite
|
Sign up to set email alerts
|

Thirty years after - dramatic change in the coastal marine habitats of Kos Island (Greece), 1981-2013.

Abstract: Results of recent fieldwork were compared with data collected in 1981, taken as a reference condition. Surveys were conducted with the same method (time-based visual census along random paths), in the same sites, by the same people. Semi-quantitative inventories of conspicuous species were analysed by univariate and multivariate techniques. Available information on the main potential stressors indicated that a regime shift has occurred in these 30+ years: sea surface temperature rose by1-2°C, human pressure gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 45 publications
1
79
0
1
Order By: Relevance
“…Along the Aegean Turkish coasts, the species is present in the Southeastern coasts (Akın et al, 2005;Öğretmen et al, 2005;Oz et al, 2007), and also up to the North (Eryilmaz, 2003). Studies based on data including last three decades showed that seawater temperature increased approximately 1-2°C (PancucciPapadopoulou et al, 2012;Bianchi et al, 2014) and warming trend is 0.06°C/year in the south Aegean Sea Skliris et al, 2011, Shaltout andOmstedt, 2014). As it is well known, the SST gradient of whole Aegean subbasin is significantly controlled by water exchange between cold/fresh Black Sea water entering through the Dardanelles Strait and warm/saline Levantine basin water entering through the Cretan Arc Straits (Zervakis et al, 2000;Poulain et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Along the Aegean Turkish coasts, the species is present in the Southeastern coasts (Akın et al, 2005;Öğretmen et al, 2005;Oz et al, 2007), and also up to the North (Eryilmaz, 2003). Studies based on data including last three decades showed that seawater temperature increased approximately 1-2°C (PancucciPapadopoulou et al, 2012;Bianchi et al, 2014) and warming trend is 0.06°C/year in the south Aegean Sea Skliris et al, 2011, Shaltout andOmstedt, 2014). As it is well known, the SST gradient of whole Aegean subbasin is significantly controlled by water exchange between cold/fresh Black Sea water entering through the Dardanelles Strait and warm/saline Levantine basin water entering through the Cretan Arc Straits (Zervakis et al, 2000;Poulain et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Given, however, the strong alterations in ecosystem structure, the establishment of the MPA will have to be accompanied by early restoration actions targeting the decrease (and if possible removal) of invasive species. Therefore, priority should be given to management measures for the regulation of the two herbivore fishes that have led to severe deforestation of the infralittoral rocky shores of Santorini Island, as well as other locations in the southern Aegean Sea (Bianchi et al, 2014;Vergés et al, 2014;authors' unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…At Kos Island (Greece, eastern Mediterranean), Bianchi et al [118] compared benthic data collected in 1981 and in 2013, by the same persons with the same method. During this 30+ year period, increases in Sea Surface Temperature (SST, +1-2°C), human pressure (resorts and hotels, 15 to 163 beds/km²), and NISs (e.g.…”
Section: Mediterranean Species and Ecosystemsmentioning
confidence: 99%